Factors Associated with the Need for Intensive Care Unit Admission Following Supratentorial Intracerebral Hemorrhage: The Triage ICH Model - Klaas, James P; Braksick, Sherri; Mandrekar, Jay; Sedova, Petra; Bellolio, M Fernanda; Rabinstein, Alejandro A; Brown, Robert D (Neurocritical care, 2017)
BACKGROUND: Providing the correct level of care for patients with intracerebral hemorrhage (ICH) is crucial, but the level of care needed at initial presentation may not be clear. This study evaluated factors associated with admission to intensive care unit (ICU) level of care. METHODS: This is an observational study of all adult patients admitted to our institution with non-traumatic supratentorial ICH presenting within 72 h of symptom onset between 2009-2012 (derivation cohort) and 2005-2008 (validation cohort). Factors associated with neuroscience ICU admission were identified via logistic regression analysis, from which a triage model was derived, refined, and retrospectively validated. RESULTS: For the derivation cohort, 229 patients were included, of whom 70 patients (31 %) required ICU care. Predictors of neuroscience ICU admission were: younger age [odds ratio (OR) 0.94, 95 % CI 0.91-0.97; p = 0.0004], lower Full Outline of UnResponsiveness (FOUR) score (0.39, 0.28-0.54; p < 0.0001) or Glasgow Coma Scale (GCS) score (0.55, 0.45-0.67; p < 0.0001), and larger ICH volume (1.04, 1.03-1.06; p < 0.0001). The model was further refined with clinician input and the addition of intraventricular hemorrhage (IVH). GCS was chosen for the model rather than the FOUR score as it is more widely used. The proposed triage ICH model utilizes three variables: ICH volume ≥30 cc, GCS score <13, and IVH. The triage ICH model predicted the need for ICU admission with a sensitivity of 94.3 % in the derivation cohort [area under the curve (AUC) = 0.88; p < 0.001] and 97.8 % (AUC = 0.88) in the validation cohort. CONCLUSIONS: Presented are the derivation, refinement, and validation of the triage ICH model. This model requires prospective validation, but may be a useful tool to aid clinicians in determining the appropriate level of care at the time of initial presentation for a patient with a supratentorial ICH.
Keywords: jednotky intenzivní péče; Intracerebral hemorrhage; Female; ženské pohlaví; Models, Neurological; modely neurologické; lidé; Patient Admission; Cerebral Intraventricular Hemorrhage; intraventrikulární krvácení do mozku; Aged, 80 and over; Cerebral Hemorrhage; Intensive Care Units; Glasgowská stupnice následků; Intensive care; příjem pacientů; Triage; cerebrální krvácení; retrospektivní studie; Male; Aged; lidé středního věku; třídění pacientů; senioři nad 80 let; Glasgow Outcome Scale; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans